Análisis de riesgos financieros en empresas de aseguradoras ecuatorianas frente a la volatilidad económica en el periodo 2022-2024 ubicadas en el Distrito Metropolitano de Quito - Obando Chantre, Ronny Josue (2025)
This article focuses on the analysis of the financial risks faced by Ecuadorian insurance companies during the period 2022-2024. This research is mainly focused on insurers in the metropolitan district of Quito. During the period under review, the insurance sector faced economic volatility that was being affected by factors such as rising inflation, citizen insecurity, and the slowdown in economic growth. These factors led to certain considerable and challenging changes in solvency, profitability, liquidity, and risk management in insurers. It can be determined that during this period, insurers not only allowed themselves and focused on readjusting reserve provision and reinsurance policies, but also had to take certain measures to protect financial stability and reevaluate their financial and operational management strategies. In addition, the regulatory framework issued by the Superintendency of Companies, Securities and Insurance was analyzed, taking into account an analysis of how it has contributed to the financial improvement of the insurance sector. For this reason, this study is intended to identify the main risks arising from this economically unstable environment, evaluate the strategies that insurers adopted and thus determine how they have managed to minimize these risks, and what mechanisms were effective. To develop this research and arrive at certain results, a field study was conducted in which surveys were applied. These were given with the purpose of knowing a real experience of how insurance companies manage financial risks through adverse economic conditions. It was possible to collect how insurers were able to cope with the economic instability that was going through. These surveys allowed to identify variations in indicators such as liquidity, technical margin, net premiums written, and claims.